2016
DOI: 10.4028/www.scientific.net/msf.846.126
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Er<sup>3+</sup> and Nd<sup>3+</sup> Doped Lithium Niobate Tellurite Glass

Abstract: Optimizing the rare earth doping in inorganic binary glasses for tuneable structural and optical properties is ever-demanding for lasing glass. A series of Er3+ and Nd3+ doped lithium niobate tellurite glasses with compositions of (70-x-y)TeO2–15Li2CO3–15Nb2O5–(x)Er2O3–(y)Nd2O3, where x = 0.0, 1.0 mol % and 0 ≤ y ≤ 1.0 mol% are synthesized using melt-quench technique. Influence of Nd3+ ion concentrations on physical and optical behaviour is examined. X–Ray diffraction pattern confirm the amorphous nature of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tellurite glasses own two forms of the basic structural unit, TeO 3 trigonal pyramid (tp) and TeO 4 trigonal bi-pyramid (tbp) [ 11 ]. It is difficult to synthesize a stable tellurium dioxide glass under normal conditions without adding a secondary component, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurite glasses own two forms of the basic structural unit, TeO 3 trigonal pyramid (tp) and TeO 4 trigonal bi-pyramid (tbp) [ 11 ]. It is difficult to synthesize a stable tellurium dioxide glass under normal conditions without adding a secondary component, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The glass hosts are excellent candidate for laser applications due to their low cost as well as ease to fabricate in various geometries [5]. In the literature there are relatively few reports on the structural properties of glass doped with Nd 3+ ions [6,7]. Recently study reported on the effects produced by the codoping with silver nitrate of glasses doped with various RE ions on the structural properties [8] that confer potential applications for these material.…”
Section: Introductionmentioning
confidence: 99%